Management of National Paralympic Committee Indonesia (NPCI) of High- Performance Sport in Klaten Regency - Zuhriyah, Anni; Kristiyanto, Agus; Purnama, Sapta Kunta (International Journal of Psychosocial Rehabilitation, 2020)
This study aims at exploring and analyzing the management of sports coaching for athletes with disabilities in the National Paralympic Committee Indonesia (NPCI) of Klaten Regency. The current study also examines the factors that support and inhibit the NPCI of Klaten Regency in sports coaching. A descriptive qualitative approach was employed as the research method. The data was obtained through interviews, observations, and literature reviews. The interactive model analysis was performed to analyze the data. A purposive sampling technique was conducted to the management of the organization, trainers, and athletes. The results of this study outline the planning, organizing, actuating, and controlling steps done by management. The supporting factors of the Management of NPCI in Klaten Regency are the full support from the government in terms of sports facilities and assistance in the procurement of facilities and infrastructure from the private sector. The inhibiting factors of the management were the lack of human resources in terms of athletes and coaches who meet the NPCI criteria and the minimal financial support that was channeled through Regional Revenue and Expenditure Budget (APBD). It can be concluded that the NPCI of Klaten Regency had carried out good organizational management by collaborating with various parties concerned with the development of sports in Klaten Regency. To summarize, the management of coaching for athletes with disabilities was well programmed.